Sport injury profiles, training and rehabilitation issues in American sports - Luckstead, E. F.; Satran, A. L.; Patel, D. R. (Pediatric Clinics of North America, 2002)
The injury profiles and possibilities for the sport-specific injuries associated with the major American youth sports have been reviewed in this article. Guideline concepts for physicans, athletes, and their families are noted. Weight-training general concepts are suggested for the younger athlete. Strong consideration should be given to include cheerleading as a sport to promote safety and reduce cheerleading-related injuries. A special appendix section updates current information on the popular sport of roller-blading.